Aromatic thermosetting liquid crystal fiber and preparation method thereof
A pot of melting clustering reaction was performed by using the liquid crystal hybrid at the sealing end of the acetylene activity group, and the thermosetry liquid crystal fiber was made through the melting spinning method to solve the problem of low and poor processing of the existing thermoplastic liquid crystal polymer, and realized the poor processing. High -intensity, excellent flame retardant performance and the effect of simplified preparation process.
Patent Information
- Application Number
- CN202211042256.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2019-08-28
- Publication Date
- 2025-01-24
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The glass transition temperature (Tg) of existing thermoplastic liquid crystal polymers is low, easy to de-orientate, and the high addition of nanofillers leads to poor processability.
Using acetylene, phenylacetylene or silyl acetylene reactive group-terminated liquid crystal oligomer, the reactive liquid crystal oligomer is obtained through a one-pot melt polycondensation reaction, and the thermosetting liquid crystal fiber is made through a melt spinning method.
It significantly increases the glass transition temperature (Tg) of liquid crystal fiber, expands the scope of application, simplifies the fiber preparation process, avoids solvent recovery problems, and gives the fiber high strength, excellent flame retardant properties and good corrosion resistance.
Smart Images

Figure CN115490629B_ABST
Abstract
Description
Technical Field
[0001] The present invention is a divisional application with application number 201910803586.8, invention name: Aromatic thermosetting liquid crystal fiber and preparation method thereof, and application date August 28, 2019. Background Art
[0002] In the early 1960s, researchers used a low-temperature polycondensation reaction method to prepare para-substituted all-aromatic amide polymers using p-aminobenzoyl chloride as raw material. This all-aromatic amide polymer is a liquid crystal polymer with excellent spinnability. This discovery led to the advent of fiber products such as Kevlar, which have the characteristics of high temperature resistance, high strength and high modulus. However, all-aromatic amide polymers need to be dissolved in concentrated sulfuric acid to make lyotropic liquid crystals and solution spinning. The spinning process is relatively complicated and there is also the problem of solvent recovery. Therefore, thermotropic liquid crystal fibers have attracted greater interest from researchers in various countries (see literature: Picken, SJ, Sikkema, DJ, Boerstoel, H, Dingemans, TJ, van der Zwaag, S, Liquid crystal main-chain polymers for high-performance fiber applications [J]. Liquid Crystals, 2011, 38 (11-12): 1591-1605).
[0003] In the late 1970s, people began to conduct basic research on thermotropic liquid crystal fibers, and in the 1980s, industrial production was already underway. The most successful of these was Vectra, developed by Celanese in the United States. TM series of thermotropic liquid crystal fibers. However, Vectra TMThe series and other thermotropic liquid crystal fibers belong to thermoplastic polymers, and their glass transition temperatures (Tg) are all lower than 120°C, which limits their use temperature and application fields. For example, CN 102443873 A discloses an aromatic copolyester liquid crystal fiber and a preparation method thereof. In order to form a highly ordered microfiber structure of the aromatic polyester polymer, the primary fiber needs to be treated with a stable heated inert gas containing non-ionic substances after spinning, pre-treated by heating and soaking in an inorganic halide solution, and then heat-treated. However, this method does not improve its Tg, and the prepared polyester liquid crystal fiber still belongs to a thermoplastic polymer, and the molecular chain in a straight state at high temperature will be deoriented. CN 102115597 A discloses a composite material for a substrate including an inorganic filler with a negative thermal expansion coefficient and a liquid crystal thermosetting oligomer. The introduction of a more rigid nanofiller does not achieve the purpose of increasing the Tg of the liquid crystal polymer. At the same time, since the amount of nanofiller added is usually high (>10vol%), it brings difficulties to the molding and processing of the liquid crystal polymer. Therefore, how to increase Tg without destroying the processability of liquid crystal fibers is still a difficult problem facing researchers. Summary of the invention
[0004] The technical problem to be solved by the present invention is to provide an aromatic thermosetting liquid crystal fiber and a preparation method thereof, which overcomes the technical defects of the prior art thermoplastic liquid crystal polymer, such as low Tg, easy deorientation, and poor processability caused by high addition of nanofillers. The rigid main chain mesogen of the liquid crystal fiber of the present invention is composed of AA, BB or AB type monomers containing ester bonds, amide bonds, imide bonds or ether bonds or a combination thereof, and the main chain is terminated by active groups such as acetylene, phenylacetylene or silylacetylene, and a reactive liquid crystal oligomer is prepared by a one-pot melt polycondensation reaction, and the molecular weight is between 1000 and 10000 g / mol, and the obtained reactive liquid crystal oligomer is made into a thermosetting liquid crystal fiber by a melt spinning method.
[0005] A liquid crystal oligomer as shown in general formula I of the present invention,
[0006]
[0007] Wherein, X is a liquid crystal main chain composed of AA, BB or AB type monomers containing ester bonds, amide bonds, imide bonds or ether bonds or a combination thereof; wherein E and E' are independently selected from acetylene, phenylacetylene or silylacetylene active groups.
[0008] Said E and E' are independently selected from:
[0009]
[0010] wherein Y is an amino group, an imino group; Z is a hydroxyl group, a carboxyl group, an ether group or a carbon group; and R, R' and R" are independently selected from hydrogen, an alkyl group containing six or fewer carbon atoms, an aryl group containing less than ten carbon atoms, a lower alkoxy group containing six or fewer carbon atoms, a lower aryloxy group containing ten or fewer carbon atoms, fluorine, chlorine, bromine or iodine.
[0011] The X is selected from:
[0012]
[0013] Furthermore, the main chain of the liquid crystal oligomer consists of only one or more structural repeating units of a benzene ring system.
[0014] The Ar1 and Ar2 are independently selected from:
[0015]
[0016] The liquid crystal oligomer is specifically selected from:
[0017] Where n = 2 to 20;
[0018] Where n = 2 to 20;
[0019] Where n = 3 to 30;
[0020] Where n = 1 to 12;
[0021] Where n = 2 to 20;
[0022] Where n = 2 to 20;
[0023] Where n=1~12.
[0024] The molecular weight of the oligomer is in the range of 1000 to 10000 g / mol.
[0025] The one-pot method for preparing a liquid crystal oligomer of the present invention comprises:
[0026] The reaction monomer, active end group and acetic anhydride solvent are added into the reactor at the same time. Under the protection of inert gas, the reaction temperature is heated from 140-150°C to 300-320°C. Then the inert gas flow is switched to vacuum and maintained for 10-30 minutes. The reaction is then cooled, ground and subjected to solid-state polycondensation reaction to obtain a liquid crystal oligomer.
[0027] The preferred method of the above preparation method is as follows:
[0028] The reactant monomer is an AA, BB or AB type monomer containing an ester bond, an amide bond, an imide bond, an ether bond or any combination thereof.
[0029] The feed ratio of the monomer to the active end group is calculated according to the predetermined oligomer molecular weight by the Carothers formula (see the literature: Carothers, WH, Polymerization [J]. Chemical Reviews, 1931, 8 (3): 353-426), that is:
[0030] The heating temperature rise rate is 0.5-1.5°C / minute; the temperature of the solid-state polycondensation reaction is 200-280°C, and the time is 12-48 hours.
[0031] The liquid crystal fiber of the present invention is obtained by pre-curing, melt-spinning and post-treating one or more of the liquid crystal oligomers.
[0032] The pre-curing is performed at 300-370° C. for 5-60 minutes; the melt spinning process parameters are as follows: one or more of the liquid crystal oligomers are melt-spun into nascent fibers, the temperature of which is maintained at 200-300° C. in a stable gas atmosphere within a distance of 5-50 cm from the spinneret, and forced cooling is performed to 15-28° C. within a distance of 50-550 cm from the spinneret; post-treatment is completed at 300-350° C.
[0033] An application of the liquid crystal fiber of the present invention.
[0034] Beneficial Effects
[0035] 1. The present invention designs and synthesizes a liquid crystal oligomer terminated by acetylene, phenylacetylene or silylacetylene active groups, the molecular weight of which is controllable, and which has a lower melting (liquid crystal phase transition) temperature, melt viscosity and better processing properties than the corresponding unterminated high molecular weight analogs;
[0036] 2. Generally, the thermal curing of the reactive model compound is carried out at a high temperature sufficient to cause crosslinking of the main chain. However, crosslinking of the main chain usually makes the cured product brittle. However, in the present invention, the reaction between the active end groups of acetylenes, phenylacetylenes or silylacetylenes can be carried out at a temperature lower than the temperature that causes significant crosslinking of the main chain of the liquid crystal polymer.
[0037] 3. The liquid crystal oligomer prepared in the present invention is melt-processed and spun into fibers. Since a cross-linked network structure is formed in the system, the Tg of the liquid crystal fiber is significantly improved, thereby expanding the application range of the liquid crystal fiber.
[0038] 4. The liquid crystal oligomer prepared by the present invention does not contain any solvent, and no small molecules are generated during the solidification process. No solvent removal is required during the bulk melt spinning process, eliminating the washing and drying steps of the existing spinning process, making the fiber preparation process simpler, more efficient and environmentally friendly;
[0039] 5. The fiber polymer chain of the present invention is a straight rigid chain, forming a highly ordered microfiber structure, and there is a strong interaction between molecules, which gives the fiber a very high strength. The network structure formed after the thermosetting reaction of the acetylene active end groups has excellent flame retardant properties and good corrosion resistance, making the fiber more suitable for harsh environments. It has great potential to serve in the fields of high-performance composite material reinforcements, marine ropes, optical cable reinforcements, etc. BRIEF DESCRIPTION OF THE DRAWINGS
[0040] Figure 1 It is a schematic diagram of the synthesis reaction process of the aromatic thermotropic liquid crystal polyester amide oligomer and polymer provided in Example 1 of the present invention and Comparative Example 1;
[0041] Figure 2 is a hot stage polarizing microscope micrograph of the aromatic thermotropic liquid crystal oligomer of Example 1;
[0042] Figure 3 This is a hot stage polarizing microscope micrograph of the aromatic thermotropic liquid crystal uncapped polymer of Comparative Example 1;
[0043] Figure 4 is a SEM image of the aromatic thermosetting thermotropic liquid crystal fiber of Example 1;
[0044] Figure 5 is a SEM image of the aromatic thermoplastic thermotropic liquid crystal fiber of Comparative Example 1;
[0045] Figure 6 is the dynamic mechanical analysis (DMTA) storage modulus (E') curve of the aromatic thermosetting and thermoplastic thermotropic liquid crystal fibers in Example 1 and Comparative Example 1;
[0046] Figure 7 is the dynamic mechanical analysis (DMTA) loss modulus (E") curve of the aromatic thermosetting and thermoplastic thermotropic liquid crystal fibers in Example 1 and Comparative Example 1;
[0047] Figure 8 : is the differential scanning calorimetry (DSC) curve of the aromatic thermotropic liquid crystal polyester amide and polyester oligomer provided in Examples 1, 3 and 4 and the aromatic thermotropic liquid crystal polyester amide polymer powder sample provided in Comparative Example 1;
[0048] Fig. 9It is a composite viscosity-time curve of the aromatic thermotropic liquid crystal polyester amide and polyester oligomer provided in Examples 1 and 4 of the present invention and the aromatic thermotropic liquid crystal polyester amide polymer powder sample provided in Comparative Example 1 at a constant temperature of 330° C. for 80 minutes;
[0049] Fig.10 This is a flow chart of preparing liquid crystal fibers by melt spinning of aromatic thermotropic liquid crystal oligomers in Example 1 of the present invention. DETAILED DESCRIPTION
[0050] The present invention will be further described below in conjunction with specific embodiments. It should be understood that these embodiments are only used to illustrate the present invention and are not intended to limit the scope of the present invention. In addition, it should be understood that after reading the content taught by the present invention, those skilled in the art can make various changes or modifications to the present invention, and these equivalent forms fall within the scope limited by the appended claims of the application equally.
[0051] Testing method of intrinsic viscosity in the embodiments: In Examples 1-7 of the present invention and Comparative Example 1, an aromatic thermotropic liquid crystal polymer or oligomer is dissolved in pentafluorophenol to prepare a 0.5 g / dL solution, and the intrinsic viscosity is measured at 60°C using an Ubbelohde viscometer method.
[0052] In Examples 1-7 of the present invention and Comparative Example 1, the raw materials used were purchased from Shanghai Bailingwei Chemical Technology Co., Ltd., 100 g / bottle, with a purity of >98%.
[0053] Example 1
[0054] 1. Preparation of aromatic thermotropic liquid crystal polyester amide oligomers
[0055] In a 250 ml three-necked round-bottom flask, add 4.15 g of terephthalic acid, 47.05 g of 2,6-naphthalene diol, 5.86 g of 3-aminophenylacetylene, 50 ml of acetic anhydride and 4 mg of potassium acetate. The flask is equipped with a sealed glass paddle stirrer, a nitrogen inlet tube and an insulated distillation head. A moderate nitrogen flow is introduced, and the reaction mixture is heated in a quicksand bath for 4 hours, and the reaction temperature rises from 140°C to 310°C. At this time, the reaction system is slowly evacuated to a vacuum and maintained for 30 minutes. The opaque melt is cooled to room temperature, the product is removed from the flask, and ground into a fine powder. A solid-state polycondensation reaction is carried out in a vacuum oven at 250°C for 24 hours to obtain an aromatic thermotropic liquid crystal polyester amide oligomer (characteristic viscosity = 0.5 dL / g). The melt polycondensation reaction process is shown in FIG. Figure 1 Route B.
[0056] 2. Preparation of aromatic thermotropic liquid crystal polyester amide fibers
[0057] The prepared liquid crystal oligomer was put into a small twin-screw extruder and pre-cured at 300°C for 30 minutes. After the melt was ejected from the spinneret, it formed a melt stream and solidified in the air below the spinneret. The nascent fiber passed through a stable nitrogen atmosphere at a distance of 25 cm from the spinneret. The temperature of the gas atmosphere was maintained at 300°C by external heating, and forced to cool to 25°C at a distance of 50 cm from the spinneret. The winding speed was 100m / min and the nozzle stretch ratio was 5. Finally, an aromatic thermosetting thermotropic liquid crystal polyesteramide fiber was obtained by post-treatment at 350°C for 20 minutes.
[0058] Comparative Example 1
[0059] 1. Preparation of aromatic thermotropic liquid crystal polyester amide polymer
[0060] In a 250 ml three-necked round-bottom flask, add 4.15 g of terephthalic acid, 47.05 g of 2,6-naphthalene diol, 50 ml of acetic anhydride and 4 mg of potassium acetate. The flask is equipped with a sealed glass paddle stirrer, a nitrogen inlet tube and an insulated distillation head. A moderate nitrogen flow is introduced, and the reaction mixture is heated in a quicksand bath for 4 hours, and the reaction temperature rises from 140°C to 310°C. At this time, the reaction system is slowly evacuated to a vacuum and maintained for 30 minutes. The opaque melt is cooled to room temperature, and the product is removed from the flask and ground into a fine powder. A solid-state polycondensation reaction is carried out in a vacuum oven at 250°C for 24 hours to obtain an aromatic thermotropic liquid crystal unterminated polyester amide polymer (characteristic viscosity = 0.95 dL / g). The melt polycondensation reaction process is shown in FIG. Figure 1 Route A.
[0061] 2. Preparation of aromatic thermotropic liquid crystal polyester amide fibers
[0062] The prepared liquid crystal polymer was put into a small twin-screw extruder and kept at 300°C for about 10 minutes to form a homogeneous melt. After being ejected from the spinneret, a thin melt flow was formed and solidified in the air below the spinneret. The nascent fiber passed through a stable nitrogen atmosphere at a distance of 25 cm from the spinneret. The temperature of the gas atmosphere was kept at 300°C by external heating, and forced to cool to 25°C at a distance of 50 cm from the spinneret. The winding speed was 100 m / min and the nozzle stretch ratio was 5. Finally, an aromatic thermoplastic thermotropic liquid crystal polyesteramide fiber was obtained by post-treatment at 350°C for 20 minutes.
[0063] The schematic diagram of the synthesis reaction of the aromatic thermotropic liquid crystal polyester amide oligomer and polymer provided in Example 1 and Comparative Example 1 of the present invention is as follows: Figure 1 As shown, the reaction is a high temperature melt polycondensation reaction.
[0064] The hot stage polarizing microscope micrograph of the aromatic thermotropic liquid crystal polyester amide oligomer of Example 1 provided by the present invention at 300°C is as follows: Figure 2 As shown, it exhibits a typical nematic liquid crystal schlieren texture and has good fluidity.
[0065] The hot stage polarizing microscope micrograph of the aromatic thermotropic liquid crystal polyester amide polymer of Comparative Example 1 provided by the present invention at 300°C is as follows: Figure 3 As shown, it also exhibits a typical nematic liquid crystal schlieren texture and good fluidity.
[0066] The SEM image of the aromatic thermosetting thermotropic liquid crystal polyester amide fiber prepared in Example 1 provided by the present invention is as follows: Figure 4 As shown, it can be seen that the fiber size is uniform, with a diameter of about 0.8 to 1 μm.
[0067] The SEM image of the aromatic thermoplastic thermotropic liquid crystal polyester amide fiber prepared in Comparative Example 1 provided by the present invention is as follows: Figure 5 As shown, it can be seen that the uniformity of fiber size is slightly worse than that of the example, with a diameter of about 0.2 to 1 μm, indicating that the polyester amide oligomer of Example 1 has better spinning stability.
[0068] The storage modulus curve comparison diagram of the aromatic thermotropic liquid crystal polyester amide fiber prepared in Comparative Example 1 and Example 1 provided by the present invention is as follows: Figure 6 As shown. Their storage moduli are all 6 GPa at 25°C. The storage modulus of Comparative Example 1 decreases significantly with increasing temperature, especially when reaching its crystalline-liquid crystal transition temperature T (K-N) When the temperature is above 1000 °C, the storage modulus drops rapidly, causing the sample to break. Example 1 has a more stable relationship between the storage modulus and temperature. When the temperature is lower than its glass transition temperature (Tg), the storage modulus remains basically unchanged; when the temperature is higher than Tg, the sample enters the rubber state, and its storage modulus remains at 100 Mpa. This is due to the presence of a cross-linked network structure in the thermosetting thermotropic liquid crystal polyester amide fiber.
[0069] The loss modulus curve comparison diagram of the aromatic thermotropic liquid crystal polyester amide fiber prepared in Comparative Example 1 and Example 1 provided by the present invention is as follows: Figure 7 As shown in FIG. 1 , the present invention defines the peak value of the loss modulus curve as the Tg of the fiber. The Tg of the former (Comparative Example 1) is about 110°C, while the Tg of the latter (Example 1) is as high as 240°C due to the presence of a cross-linked network structure. Although the Tg values of CN102443873 A and CN 102115597 A are not disclosed, the thermotropic liquid crystal polymer in CN 102443873 A is similar to that of Vectra TMThe series are the same, and their Tg values are all lower than 120°C; and from the thermal expansion coefficient test curve of CN 102115597 A, it can be seen that the Tg values of its various samples are all lower than 200°C, which shows that the present invention overcomes the technical defect of the prior art that the thermoplastic liquid crystal polymer has a low Tg.
[0070] The above data indicate that the aromatic thermosetting thermotropic liquid crystal fiber disclosed in the present invention overcomes the disadvantage of low Tg existing in the existing aromatic thermoplastic thermotropic liquid crystal fiber and has good spinning stability and fiber size uniformity.
[0071] Example 2
[0072] 1. Preparation of aromatic thermotropic liquid crystal polyester oligomers
[0073] In a 250 ml three-necked round bottom flask, add 4.15 g of terephthalic acid, 37.24 g of 4,4'-dihydroxybiphenyl, 5.86 g of 3-aminophenylacetylene, 50 ml of acetic anhydride and 5 mg of sodium acetate. The flask is equipped with a sealed glass paddle stirrer, a nitrogen inlet tube and an insulated distillation head. A moderate nitrogen flow is introduced, and the reaction mixture is heated in a quicksand bath for 5 hours, and the reaction temperature rises from 140°C to 320°C. At this time, the reaction system is slowly evacuated to a vacuum and maintained for 30 minutes. The opaque melt is cooled to room temperature, the product is removed from the flask, and ground into a fine powder. Solid-state polycondensation reaction is carried out in a vacuum oven at 260°C for 24 hours to obtain an aromatic thermotropic liquid crystal polyester oligomer (intrinsic viscosity = 0.65 dL / g).
[0074]
[0075] 2. Preparation of aromatic thermotropic liquid crystal polyester fibers
[0076] The prepared liquid crystal oligomer was put into a small twin-screw extruder and pre-cured at 310°C for 30 minutes. The melt was ejected from the spinneret to form a melt stream, which was solidified and formed in the air below the spinneret. The nascent fiber passed through a stable nitrogen atmosphere at a distance of 45 cm from the spinneret. The temperature of the gas atmosphere was maintained at 200°C by external heating, and forced to cool to 15°C at a distance of 550 cm from the spinneret. The winding speed was 200m / min and the nozzle stretch ratio was 6. Finally, an aromatic thermosetting thermotropic liquid crystal polyester fiber was obtained by post-treatment at 300°C for 60 minutes.
[0077] Example 3
[0078] 1. Preparation of aromatic thermotropic liquid crystal polyester oligomers
[0079] In a 500 ml three-necked round-bottom flask, add 100.83 g of 4-p-hydroxybenzoic acid, 50.80 g of 6-acetoxy-2-naphthoic acid, 10.14 g of N-(4-carboxyphenyl)-4-phenylethynylphthalimide, 10.53 g of N-(4-acetoxyphenyl)-4-phenylethynylphthalimide, 150 ml of acetic anhydride and 10 mg of potassium acetate. The flask is equipped with a sealed glass paddle stirrer, a nitrogen inlet tube and an insulated distillation head. A moderate nitrogen flow is introduced, and the reaction mixture is heated in a quicksand bath for 4 hours, and the reaction temperature rises from 150°C to 310°C. At this time, the reaction system is slowly evacuated to a vacuum and maintained for 30 minutes. The opaque melt is cooled to room temperature, the product is removed from the flask, and ground into a fine powder. The solid-state polycondensation reaction was carried out in a vacuum oven at 250° C. for 24 hours to obtain an aromatic thermotropic liquid crystal polyester oligomer (intrinsic viscosity = 0.55 dL / g).
[0080]
[0081] 2. Preparation of aromatic thermotropic liquid crystal polyester fibers
[0082] The prepared liquid crystal oligomer was put into a small twin-screw extruder and pre-cured at 350°C for 5 minutes. After the melt was ejected from the spinneret, it formed a melt stream and solidified in the air below the spinneret. The nascent fiber passed through a stable nitrogen atmosphere at a distance of 50 cm from the spinneret. The temperature of the gas atmosphere was maintained at 300°C by external heating, and forced to cool to 28°C at a distance of 50 cm from the spinneret. The winding speed was 1000m / min and the nozzle stretch ratio was 15. Finally, an aromatic thermosetting thermotropic liquid crystal polyester fiber was obtained by post-treatment at 320°C for 40 minutes.
[0083] Example 4
[0084] 1. Preparation of aromatic thermotropic liquid crystal polyester oligomers
[0085] In a 250 ml three-necked round-bottom flask, 16.61 g of terephthalic acid, 16.61 g of isophthalic acid, 82.87 g of 4-p-hydroxybenzoic acid, 37.24 g of 4,4'-dihydroxybiphenyl, 2.52 g of N-(4-carboxyphenyl)-4-phenylethynylphthalimide, 2.61 g of N-(4-acetylphenol)-4-phenylethynylphthalimide, 130 ml of acetic anhydride and 5 mg of sodium acetate were added. The flask was equipped with a sealed glass paddle stirrer, a nitrogen inlet tube and an insulated distillation head. A moderate nitrogen flow was introduced and the reaction mixture was heated in a quicksand bath for more than 6 hours, and the reaction temperature rose from 145°C to 300°C. At this time, the reaction system was slowly evacuated and maintained for 30 minutes. The opaque melt was cooled to room temperature, the product was removed from the flask and ground into a fine powder. The solid-state polycondensation reaction was carried out in a vacuum oven at 270° C. for 24 hours to obtain an aromatic thermotropic liquid crystal polyester oligomer (intrinsic viscosity = 0.75 dL / g).
[0086]
[0087] 2. Preparation of aromatic thermotropic liquid crystal polyester fibers
[0088] The prepared liquid crystal oligomer was put into a small twin-screw extruder and pre-cured at 310°C for 30 minutes. After the melt was ejected from the spinneret, it formed a melt stream and solidified in the air below the spinneret. The nascent fiber passed through a stable nitrogen atmosphere at a distance of 45 cm from the spinneret. The temperature of the gas atmosphere was maintained at 200°C by external heating, and forced to cool to 15°C at a distance of 550 cm from the spinneret. The winding speed was 200m / min and the nozzle stretch ratio was 12. Finally, an aromatic thermosetting thermotropic liquid crystal polyester fiber was obtained by post-treatment at 300°C for 60 minutes.
[0089] See attached Figure 8 , which is the DSC curve of the aromatic thermotropic liquid crystal polyester amide and polyester oligomer provided in Examples 1, 3, and 4 of the present invention and the aromatic thermotropic liquid crystal polyester amide polymer powder sample provided in Comparative Example 1. It can be seen that the melting point of the aromatic thermotropic liquid crystal polyester amide prepared in Comparative Example 1 is about 330°C, while the melting points of the aromatic thermotropic liquid crystal polyester amide and polyester oligomer prepared in Examples 1, 3, and 4 are significantly reduced, and the melting peak area is significantly reduced. This is because the addition of different types of aromatic monomers (amides) or asymmetric structure monomers (isophthalic acid) destroys the symmetry of the molecular chain, greatly reduces the crystallinity of the polymer, and introduces more amorphous phases into the system. The introduction of aromatic acetylene active end groups shortens the molecular chain length, effectively reduces melting (liquid crystal phase transition), and improves processability.
[0090] See attached Fig. 9, which is the composite viscosity-time curve of the aromatic thermotropic liquid crystal polyester amide and polyester oligomer provided in Examples 1 and 4 of the present invention and the aromatic thermotropic liquid crystal polyester amide polymer powder sample provided in Comparative Example 1 at 330°C for 80 minutes. As can be seen from the figure, the aromatic thermotropic liquid crystal polyester amide obtained in Comparative Example 1 has a slight decrease in viscosity and then increases after being kept at 330°C for 25 minutes, because it undergoes further polycondensation reaction at this temperature, resulting in an increase in molecular weight. The aromatic thermotropic liquid crystal polyester amide and polyester oligomer obtained in Examples 1 and 4 begin to decrease in viscosity at the initial stage of 330°C, and their minimum viscosity value is 1 / 15 to 1 / 10 of the minimum viscosity value of Comparative Example 1, which is mainly due to the introduction of aromatic acetylene active end groups to shorten the molecular chain length. Although the aromatic thermotropic liquid crystal polyester amide and polyester oligomer obtained in Examples 1 and 4 begin to increase in viscosity at 330°C for 30 minutes because the aromatic acetylene active end groups undergo cross-linking and curing reaction, resulting in an increase in molecular weight, such a melting window is sufficient to complete processing and molding.
[0091] See attached Fig.10 , which is a flow chart of preparing liquid crystal fibers by melt spinning of aromatic thermotropic liquid crystal oligomers in Example 1 of the present invention.
[0092] Example 5
[0093] 1. Preparation of aromatic thermotropic liquid crystal polyester amide oligomers
[0094] In a 250 ml three-necked round-bottom flask, add 41.53 g of terephthalic acid, 37.79 g of 4-acetamidophenol, 94.09 g of 6-acetoxy-2-naphthoic acid, 2.20 g of N-(4-carboxyphenyl)-4-phenylethynylphthalimide, 2.29 g of N-(4-acetoxyphenol)-4-phenylethynylphthalimide, 105 ml of acetic anhydride and 5 mg of sodium acetate. The flask is equipped with a sealed glass paddle stirrer, a nitrogen inlet tube and an insulated distillation head. A moderate nitrogen flow is introduced, and the reaction mixture is heated in a quicksand bath for 3 hours, and the reaction temperature rises from 150°C to 300°C. At this time, the reaction system is slowly evacuated and maintained for 25 minutes. The opaque melt is cooled to room temperature, the product is removed from the flask, and ground into a fine powder. The solid-state polycondensation reaction was carried out in a vacuum oven at 230° C. for 48 hours to obtain an aromatic thermotropic liquid crystal polyester amide oligomer (intrinsic viscosity = 0.64 dL / g).
[0095] 2. Preparation of aromatic thermotropic liquid crystal polyester amide fibers
[0096] The prepared liquid crystal oligomer was put into a small twin-screw extruder and pre-cured at 390°C for 5 minutes. After the melt was ejected from the spinneret, it formed a melt stream and solidified in the air below the spinneret. The nascent fiber passed through a stable nitrogen atmosphere at a distance of 45 cm from the spinneret. The temperature of the gas atmosphere was maintained at 200°C by external heating, and forced to cool to 15°C at a distance of 250 cm from the spinneret. The winding speed was 400m / min and the nozzle stretch ratio was 5. Finally, an aromatic thermosetting thermotropic polyester amide liquid crystal fiber was obtained by post-treatment at 300°C for 40 minutes.
[0097]
[0098] Example 6
[0099] 1. Preparation of aromatic thermotropic liquid crystal polyester imide oligomers
[0100] In a 250 ml three-necked round-bottom flask, add 20.66 g of N-(3'-phenol) trimellitic acid imide, 23.51 g of 4-p-hydroxybenzoic acid, 16.94 g of 6-acetyl-2-naphthoic acid, 4.19 g of N-(4-carboxyphenyl)-dimethylsilyl-1,4-tolane, 4.347 g of N-(4-acetylphenol)-dimethylsilyl-1,4-tolane, 130 ml of acetic anhydride and 6 mg of sodium acetate. The flask is equipped with a sealed glass paddle stirrer, a nitrogen inlet tube and an insulated distillation head. A moderate nitrogen flow is introduced, and the reaction mixture is heated in a quicksand bath for 6 hours, and the reaction temperature rises from 143°C to 300°C. At this time, the reaction system is slowly evacuated to a vacuum and maintained for 30 minutes. The opaque melt is cooled to room temperature, the product is removed from the flask, and ground into a fine powder. The solid-state polycondensation reaction was carried out in a vacuum oven at 220° C. for 48 hours to obtain an aromatic thermotropic liquid crystal polyester imide oligomer (intrinsic viscosity = 0.76 dL / g).
[0101]
[0102] 2. Preparation of aromatic thermotropic liquid crystal polyester imide fibers
[0103] The prepared liquid crystal oligomer was put into a small twin-screw extruder and pre-cured at 310°C for 35 minutes. The melt was ejected from the spinneret to form a melt stream, which was solidified and formed in the air below the spinneret. The nascent fiber passed through a stable nitrogen atmosphere at a distance of 35 cm from the spinneret. The temperature of the gas atmosphere was maintained at 250°C by external heating, and forced to cool to 20°C at a distance of 550 cm from the spinneret. The winding speed was 600m / min, and the nozzle stretch ratio was 10. Finally, an aromatic thermosetting thermotropic liquid crystal polyesterimide fiber was obtained by post-treatment at 300°C for 60 minutes.
[0104] Example 7
[0105] 1. Preparation of aromatic thermotropic liquid crystal polyester ether oligomers
[0106] In a 500 ml three-necked round-bottom flask, add 18.27 g terephthalic acid, 18.27 g isophthalic acid, 91.16 g 4-p-hydroxybenzoic acid, 44.47 g 4,4'-dihydroxydiphenyl ether, 2.77 g N-(4-carboxyphenyl)-4-phenylethynylphthalic acid imide, 2.87 g N-(4-acetylphenol)-4-phenylethynylphthalic acid imide, 140 ml acetic anhydride and 5 mg sodium acetate. The flask is equipped with a sealed glass paddle stirrer, a nitrogen inlet tube and an insulated distillation head. A moderate nitrogen flow is introduced, and the reaction mixture is heated in a quicksand bath for 6 hours, and the reaction temperature rises from 140°C to 320°C. At this time, the reaction system is slowly evacuated and maintained for 25 minutes. The opaque melt is cooled to room temperature, the product is removed from the flask, and ground into a fine powder. The solid-state polycondensation reaction was carried out in a vacuum oven at 260° C. for 24 hours to obtain an aromatic thermotropic liquid crystal polyester ether oligomer (intrinsic viscosity = 0.82 dL / g).
[0107]
[0108] 2. Preparation of aromatic thermotropic liquid crystal polyester ether fibers
[0109] The prepared liquid crystal oligomer was put into a small twin-screw extruder and pre-cured at 310°C for 30 minutes. After the melt was ejected from the spinneret, it formed a melt stream and solidified in the air below the spinneret. The nascent fiber passed through a stable nitrogen atmosphere at a distance of 45 cm from the spinneret. The temperature of the gas atmosphere was maintained at 200°C by external heating, and forced to cool to 15°C at a distance of 250 cm from the spinneret. The winding speed was 300m / min and the nozzle stretch ratio was 15. Finally, an aromatic thermosetting thermotropic liquid crystal polyester ether fiber was obtained by post-treatment at 300°C for 60 minutes.
[0110] See Table 1, which shows the mechanical, flame retardant and corrosion resistant performance results of the aromatic thermotropic liquid crystal polyester amide, polyester, polyester imide and polyester ether fibers provided in Examples 1-7 of the present invention and the aromatic thermotropic liquid crystal polyester amide fiber provided in Comparative Example 1.
[0111] As can be seen from the table, the mechanical and flame retardant properties of various aromatic thermosetting fibers provided in Examples 1-7 are better than those of the aromatic thermoplastic fibers provided in Comparative Example 1; the corrosion resistance of various aromatic thermosetting fibers provided in Examples 1, 5, and 6 is better than that of the aromatic thermoplastic fibers provided in Comparative Example 1. Because the polymer chains of thermosetting fibers are straightened rigid chains, a highly ordered microfiber structure is formed, which is retained during the curing process, and there is a strong interaction between molecules, thus giving the fiber a high strength. At the same time, the network structure formed after the thermosetting reaction of the active end groups of acetylene has excellent flame retardancy and corrosion resistance. CN 102443873 A and CN 102115597 A do not disclose flame retardancy and corrosion resistance. In terms of mechanical properties, the polyester fiber provided by CN 102443873 A has a breaking strength (12.9-19.6 cN / dtex) comparable to the aromatic thermotropic liquid crystal polyester amide, polyester, polyester imide, and polyester ether fibers provided in Examples 1-7 of the present invention. In general, the aromatic thermotropic liquid crystal polyester amide, polyester, polyester imide, and polyester ether fibers provided in Examples 1-7 of the present invention have better comprehensive properties.
[0112] Table 1. Mechanical, flame retardant and corrosion resistant properties of the aromatic thermotropic liquid crystal polyester amide, polyester, polyester imide and polyester ether fibers provided in Examples 1-7 of the present invention and the aromatic thermotropic liquid crystal polyester amide fiber provided in Comparative Example 1:
[0113]
[0114] a GB / T 3923.1-1997 Determination of tensile properties, breaking strength and elongation at break of textiles and fabrics: Clamp the sample at the center of the clamp to ensure that the center line of the tension passes through the midpoint of the clamp. Start the tester, move the movable clamp, and stretch the sample until it breaks. Record the breaking strength in Newton (N); record the breaking elongation or breaking elongation in millimeters (mm) or percentage (%). At least 5 specimens are required in each direction. Calculate the average breaking strength and breaking elongation in the warp and weft directions (or longitudinal and transverse directions); the stretching speed is 1.0mm / min.
[0115] bGB / T5454-1997 Textile Combustion Performance Test Oxygen Index Method: The sample is placed under vertical experimental conditions, and in an upward oxygen-nitrogen mixed gas flow, the upper end of the sample is ignited to observe its combustion characteristics, and its afterburning time or damaged length is compared with the specified limit value; through a series of sample tests in different oxygen concentrations, the minimum oxygen concentration required for the sample to just maintain combustion, that is, the limiting oxygen index (LOI%), can be determined. 40% to 60% of the tested samples must exceed the specified afterburning and smoldering time or damaged length; the fiber sample length is 15cm.
[0116] c There is currently no national standard for reference. The solvent immersion method is used for testing: weigh the dry sample and record the mass m1, soak it in acidic (sulfuric acid, nitric acid, hydrochloric acid, acetic acid, etc.), alkaline (sodium hydroxide solution, etc.), and oily (gasoline, diesel, kerosene, etc.) solvents for 24 hours, take out the sample and remove the solvent, weigh it again after drying and record the mass m2, calculate the mass difference before and after the test Δm=m1-m2, and judge the corrosion resistance of the sample in turn.
Claims
1. A liquid crystal oligomer, characterized in that: The specific details are: , where n=2~20.
2. A liquid crystal fiber, characterized in that: The liquid crystal oligomer according to claim 1 is prepared by pre-curing, melt spinning and post-treatment.
3. The liquid crystal fiber according to claim 2, characterized in that: The pre-curing is performed at 300-370° C. for 5-60 minutes; the melt spinning process parameters are as follows: one or more of the liquid crystal oligomers are melt-spun into nascent fibers, the temperature of which is maintained at 200-300° C. in a stable gas atmosphere within a distance of 5-50 cm from the spinneret, and forced cooling is performed to 15-28° C. within a distance of 50-550 cm from the spinneret; post-treatment is completed at 300-350° C.
4. Use of the liquid crystal fiber according to claim 2 in high-performance composite material reinforcements, marine ropes or optical cable reinforcements.
Citation Information
Patent Citations
Composite material for substrate containing inorganic filling material and liquid crystal thermosetting oligomer with negative thermal expansion coefficient
CN102115597A
Aromatic copolyester liquid crystal fiber and its preparation method
CN102443873A
Aromatic thermosetting liquid crystal fiber and preparation method thereof
CN110498760A
Aromatic thermosetting liquid crystal fiber and preparation method thereof
CN115322135A
Liquid crystalline thermosets from ester, ester-imide and ester-amide oligomers
CN1455792A